(untitled) (Economics and region, 2023)
The article defines the concept of motorcycle tourism as an active recreation, which consists in travelling on a motorcycle on routes with tourist objects of excursion nature. The main differences of such motorcycle tours from sports motorcycle tourism, focused on obtaining sports categories and titles, are analysed - refusal to deliberately complicate the route, division of tours into categories of complexity and combination of the sports component of the tour with the inspection of cultural and natural attractions. It is substantiated that the complexity of such hikes can range from simple to extremely high, and the routes are laid out in such a way as to take advantage of the advantages offered by a motorcycle for fast movement along the route. The article briefly describes the development of tourist motorcycle traffic in the western territories of Ukraine and the problems it has encountered recently. The classification of types of motorcycles in terms of their suitability for travelling is presented. The author suggests ways to reorient the flow of motorcycle tourists to the western part of Ukraine due to the increased risk of being hit by explosive devices when travelling through the territory that was under occupation or in close proximity to the war zone. A number of attractive motorcycle tourist routes have been developed in western Ukraine during the war and post-war period.